(untitled) (MAUSAM, 1992)
. Variations in ozone amounts have been studied using data obtained with Dobson spectrophotometers during 1966-1988 at Srinagar, New Delhi, Pune and Kodaikanal. Yearly average values of total ozone , and its vertical distribution by the Umkehr method in layers 1 to 9 have been computed. Departures from compo- site avarage value for the period (1966-1988) have been computed for both total ozone and its vertical distribution. The variation over New Delhi and Pune have been compared with those at Arosa reported by Dutsch 1989). The observed variations in the ozone distribution at New Delhi and Pune can be explained, as being within normal interannual changes. Tropospheric ozone in layer lover New Delhi shows some effects of an anthropogenic nature, on the other hand Pune does not exhibit in any influence of pollutants in any layer, either in the troposphere or stratosphert.